2021
DOI: 10.1088/1361-6501/ac026f
|View full text |Cite
|
Sign up to set email alerts
|

A hybrid model of LSTM neural networks with a thermodynamic model for condition-based maintenance of compressor fouling

Abstract: Compressor fouling is one of the critical gas path faults of gas turbines, and the fouling process is significantly influenced by the quality of the inlet air coming from the air intake system with filters. The maintenance strategies for compressor fouling mainly consist of online/offline washing and replacement of filters, where optimizing the washing cycles and the replacement of filters is essential for the economy and safety of gas turbine operation as of the trade-off between the performance improvement a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…Yet, its training process often suffers from gradient disappearance or explosion. For this purpose, the long short-term memory (LSTM) was constructed to deal with the long-term dependence of the time series [41]. As its evolutionary version, the gate recurrent unit significantly reduces training time by combining input gates and forgetters into update gates [42,43].…”
Section: Deep Learning For Remaining Useful Life (Rul) Predictionmentioning
confidence: 99%
“…Yet, its training process often suffers from gradient disappearance or explosion. For this purpose, the long short-term memory (LSTM) was constructed to deal with the long-term dependence of the time series [41]. As its evolutionary version, the gate recurrent unit significantly reduces training time by combining input gates and forgetters into update gates [42,43].…”
Section: Deep Learning For Remaining Useful Life (Rul) Predictionmentioning
confidence: 99%
“…Real field data from a gas turbine power plant were used for training and testing, and it was found that this method had a smaller relative mean square error compared to other prediction methods. Y. Jin et al [21] developed a hybrid framework that integrates thermodynamic models and Long Short-Term Memory (LSTM) neural networks to predict washing cycles (remaining service life prediction) and detect filter leakage (filter diagnosis). The prediction model based on the LSTM-Hankel method exhibited good performance in long-term washing cycle prediction.…”
Section: Introductionmentioning
confidence: 99%